Exploring carbonate reservoirs potential, north Egypt - RADWAN, Mohamed Said; GOBASHY, Mohamed; DAHROUG, Said; RASLAN, Samir (Contributions to Geophysics and Geodesy, 2024)
Carbonate reservoirs contain a significant portion of the world's oil reserves. The Middle East is home to many of these reservoirs. Carbonate reservoirs can be found in a few very large oil fields, including Egypt's Zohr field, the largest conventional gas field in Egypt. In this article, we present a couple of successful tertiary carbonate reservoirs that are bearing hydrocarbon in the Egyptian Western Desert and Gulf of Suez provinces, they are distributed across Egypt's subsurface, and they are characterized by heterogeneous porosity and permeability. These heterogeneities are caused by the wide spectrum of tectonostratigraphic environments in which carbonates are deposited and by subsequent diagenetic alteration of the original rock fabric. The structural analysis of the study areas based on the interpretation of both geophysical and geological data, in JD, Abu Sennan, and the North Amer areas in the Western Desert and offshore Gulf of Suez respectively showed that tectonostratigraphic history during tertiary time affected a great extent carbonate reservoir quality. Major fault trends formed secondary fracture porosity possibly allowing hydrothermal solutions to pass through the reservoirs and form secondary vuggy porosity. These characteristics are considered important factors of promising carbonate reservoirs. In this study, several carbonate reservoirs have been outlined. The study workflow helped us better identify carbonate prospects with high fractured density.